A Case of Neurosarcoidosis with Labyrinthine Involvement. (6th March 2014) - Johnson, Peter B.; Melbourne-Chambers, Roxanne; Saindane, Amit Manohar; Desai, Nilesh; Smith, Myrton
Abstract : Sarcoidosis is a chronic granulomatous disease of unknown aetiology, which may involve any organ system. It most commonly occurs in adults with childhood involvement being rare. Central nervous system involvement is seen in up to 25% and typically involves meningeal disease resulting in multiple cranial neuropathies. Other common clinical findings include seizures, headache, dementia, and pituitary dysfunction. Imaging plays a central role in the diagnosis with typical findings including pachymeningeal and leptomeningeal enhancing lesions. Other imaging findings include lacunar and major territory infarcts, hypothalamic and infundibular thickening, hydrocephalus, and cranial nerve enhancement. We present a case of an eight-year-old male patient with progressive headache, visual disturbance, unilateral sensory hearing loss, and multiple cranial neuropathies. Imaging findings demonstrated the classic pachymeningeal and leptomeningeal enhancement along much of the skull base, as well as enhancement of the right and left second and eighth cranial nerves. Extensive inflammatory changes were noted in the temporal bones and paranasal sinuses. There was also enhancement of the right and left labyrinths. Sinus biopsy confirmed sarcoidosis. We present the first case to our knowledge of sarcoid labyrinthitis.